2017
DOI: 10.1093/neuonc/nox132
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of genetic alterations in diffuse lower-grade gliomas

Abstract: Subtype-specific genetic lesions can be used to stratify patients within each LGG subtype. enabling better prognostication and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
214
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(244 citation statements)
references
References 42 publications
17
214
2
Order By: Relevance
“…gain of chromosome 7 and loss of chromosome 10) has been reported in gliomas . Gain of chromosome 7 and loss of chromosome 10 were shown to be independent prognostic factors in IDH ‐wt LGGs adjusted for age and WHO grade . Nearly all IDH ‐wt LGGs with chromosome 7 gain and chromosome 10 loss harbored TERT promoter mutation , which was a prognostic indicator in this tumor entity based on our results.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…gain of chromosome 7 and loss of chromosome 10) has been reported in gliomas . Gain of chromosome 7 and loss of chromosome 10 were shown to be independent prognostic factors in IDH ‐wt LGGs adjusted for age and WHO grade . Nearly all IDH ‐wt LGGs with chromosome 7 gain and chromosome 10 loss harbored TERT promoter mutation , which was a prognostic indicator in this tumor entity based on our results.…”
Section: Discussionsupporting
confidence: 74%
“…After screening the abstract, 150 potential articles were selected for full-text reading and, finally, we included 11 studies comprising 911 IDH-wt LGGs for final analyses (Fig. 1) [5,[7][8][9][10][11][12][13][14][15][16]. The characteristics of these studies are described in Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…These conclusions are based on the findings that those histologic IDH-wildtype diffuse astrocytic gliomas of WHO grade II or III that carry EGFR amplification, +7/−10 or TERT promoter mutation are associated with significantly shorter patient survival compared to patients with other WHO grade II or III gliomas, and patients have outcomes similar to patients with IDH-wildtype glioblastoma [1, 2, 11, 26, 27, 32, 33]. The large majority of IDH-wildtype diffuse astrocytic gliomas of WHO grade II or III with these genetic signatures correspond histologically to anaplastic astrocytoma, WHO grade III.…”
Section: Recommended Grading Parameters: Egfr Amplification Combinedmentioning
confidence: 99%
“…BRAF V600E) may be warranted in diagnostically challenging cases [27]. Some studies have reported on gains of 7p or 7q, as well as losses of 10p or 10q as chromosomal imbalances linked to poor survival for patients with WHO grade II or III IDH-wildtype astrocytic gliomas [2, 27, 29, 32, 33]. However, most studies reported whole gains of chromosome 7 and whole losses of chromosome 10 (+7/−10), and the prognostic association of other, far less common imbalances, such as +7q/−10q, +7/−10q or +7q/−10, was not evaluated separately from +7/−10.…”
Section: Recommended Grading Parameters: Egfr Amplification Combinedmentioning
confidence: 99%
See 1 more Smart Citation